Congenital Brain Abnormalities: An Update on Malformations of Cortical Development and Infratentorial Malformations - Poretti, Andrea; Boltshauser, Eugen; Huisman, Thierry A.G.M. (Seminars in Neurology, 2014)
In the past two decades, significant progress in neuroimaging and genetic techniques has allowed for advances in the correct definition/classification of congenital brain abnormalities, which have resulted in a better understanding of their pathogenesis. In addition, new groups of diseases, such as axonal guidance disorders or tubulinopathies, are increasingly reported. Well-defined neuroimaging diagnostic criteria have been suggested for the majority of congenital brain abnormalities. Accurate diagnoses of these complex abnormalities, including distinction between malformations and disruptions, are of paramount significance for management, prognosis, and family counseling. In the next decade, these advances will hopefully be translated into deeper understanding of these disorders and more specific treatments.
Keywords: brain; malformations; disruptions; genetics; neuroimaging; children